Young drivers behaviour towards multilingual traffic signage: case of KAED and AIKOL, IIUM students driver - Bachok, Syahriah (s.n, 2012)
This paper deals with the effectiveness of traffic signs provision in International Islamic University Malaysia (IIUM), Gombak campus. Literature has identified that the effectiveness of any sign depends upon its attention, meaning, time, respect values and illumination. Some 400 questionnaire forms have been distributed to two faculties at the International Islamic University, Malaysia. The purposive sampling has been used as a method for the survey. The 400 forms included were derived from a list of students of IIUM who registered their car under supplied IIUM Traffic Unit in order to identify the perception towards the provision of the new informatory traffic sign in campus. The Univariate and Bivariate analysis explores each variable in a data set, separately. Some of the SPSS analyses that have been used were Chi-Square and Kendall Tau-b correlation. Findings from the study show that a sign must attract the visual attention of the driver at a range greater than the reading distance requirement. From the research, it has been found that gender was the factors that influence the perceptions of the respondents toward the effectiveness of traffic signs. It can be concluded that the frequency of signage observation in IIUM influenced the perceptions of respondents towards the effectiveness of traffic signs. The effectiveness of any sign depends upon its attention, meaning, time and respect value. Therefore, it is suggested that, in any event the regulation, warning, or guidance which the sign is 1 intended to convey, must appear reasonable, rational, and advantages to the road user. The basic colours that were recommended for the background colour of traffic sign is light grey and black for the lettering. Furthermore, the preferable board size is 2000-3000mm. In addition, the respondents’ preferred to have larger font size of 70-85mm, as young drivers were more attracted to the larger font size. Therefore, it is suggested that visual attention, sign lettering, legibility and maintenance of the traffic sign of findings to be improved based on the generalization of findings